Modified compression therapy in mixed arterial–venous leg ulcers: An integrative review. Issue 6 (18th March 2021) - Lim, Sheryl Li Xin; Chung, Rui En; Holloway, Samantha; Harding, Keith G.
Abstract: Leg ulcers remain an increased burden to healthcare cost and morbidity in modern society. While most leg ulcers are venous in origin, recognition and prompt identification of concomitant arterial occlusive disease is critical to determine underlying aetiology and subsequent management. This integrative review presents the current evidence to establish the role of modified compression therapy (MCT) in treatment of mixed arterial venous leg ulcers (MAVLU). A literature search was conducted using the electronic databases CINAHL, MEDLINE, PUBMED, and Embase. Ten studies met the eligibility criteria and were subsequently analysed. Our review concludes that MCT, with compression pressures between 20 and 30 mmHg, can promote healing in MAVLU with moderate arterial insufficiency (0.5 ≤ ABPI ≤0.8). If ABPI is <0.5, MCT can be considered once restoration of acceptable ABPI is achieved. Intolerance, lack of response or further deterioration of disease within 3 months should prompt further arterial imaging and intervention. MCT is generally well tolerated with no adverse outcomes reported. A holistic yet individualised approach is vital in order to account for all factors influencing this patient‐led decision‐making process, ultimately ensuring effective treatment, which improves patient's quality of life and reduces socioeconomic burden of the disease.